2021
DOI: 10.1093/rb/rbab003
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant biocompatible composite collagen dressing for diabetic wound healing in rat model

Abstract: Associated with persistent oxidative stress, altered inflammatory responses, poor angiogenesis and epithelization, wound healing in diabetic patients is impaired. N-acetylcysteine (NAC) is reported to resist excess reactive oxygen species (ROS) production, prompt angiogenesis and maturation of the epidermis. Studies have revealed that graphene oxide (GO) can regulate cellular behavior and form cross-links with naturally biodegradable polymers such as collagen (COL) to construct composite scaffolds. Here, we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 43 publications
(23 reference statements)
0
14
0
Order By: Relevance
“…As shown in Fig. 3a , C–N stretching (1451.88 cm −1 ) in the SF transferred into the new C–N (1017.68 cm −1 ); at the same time, the intensity of C–O (3339.11 cm −1 ), C = O (1634.70 cm −1 and 1249.80 cm −1 ) and N–H stretching (1543.73 cm −1 ) in the Ag–AV–SF system significantly improved compared with that in the SF [ 25 ]. The phenomenon of stretching vibration was attributed to the α-amino nitrogen and α-carboxylic oxygen from the tyrosine formed complexes with silver ions through coordination bonds [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Fig. 3a , C–N stretching (1451.88 cm −1 ) in the SF transferred into the new C–N (1017.68 cm −1 ); at the same time, the intensity of C–O (3339.11 cm −1 ), C = O (1634.70 cm −1 and 1249.80 cm −1 ) and N–H stretching (1543.73 cm −1 ) in the Ag–AV–SF system significantly improved compared with that in the SF [ 25 ]. The phenomenon of stretching vibration was attributed to the α-amino nitrogen and α-carboxylic oxygen from the tyrosine formed complexes with silver ions through coordination bonds [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thermogravimetric analysis (TGA) is a physicochemical property that could be treated as the colloidal stability of the hydrogel [ 24 , 25 ]. TGA was performed using a thermal gravimetric analyzer (TA SDT 650, TA, USA).…”
Section: Experiments Sectionmentioning
confidence: 99%
“…[26] In recent years, NAC showed extensive and far-reaching potential in the treatment of ROS-related kidney injury, myocardial injury, diabetes-related wound healing and so on. [68][69][70][71][72] In addition, NAC appears as a raw material in the synthesis of nanomaterials for a wide application, which has dabbled in the fields of drug delivery, medical imaging and so on. [73][74][75] In the microenvironment of intervertebral disc degeneration, the accumulation of ROS triggers a series of problems including mitochondrial dysfunction, NPC senescence, and the continued secretion of SASP.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found these indicators have a similar AL predictive effect as CRP. SOD and CAT are antioxidant enzymes, which constitute the primary cellular antioxidant defenses [ 43 ]. Studies have reported that the rise of SOD, CAT, and other antioxidant enzymes is an indication of tissue repair [ 44 ].…”
Section: Discussionmentioning
confidence: 99%